Inhibition of Phosphodiesterase 5 Promotes the Aromatase-Mediated Estrogen Biosynthesis in Osteoblastic Cells by Activation of cGMP/PKG/SHP2 Pathway - Wisanwattana, Wisanee; Wongkrajang, Kanjana; Cao, Dong-yi; Shi, Xiao-ke; Zhang, Zhong-hui; Zhou, Zong-yuan; Li, Fu; Mei, Qing-gang; Wang, Chun; Suksamrarn, Apichart; Zhang, Guo-lin; Wang, Fei (Frontiers in Endocrinology, 2021)
Mechanical stimulation induces bone growth and remodeling by the secondary messenger, cyclic guanosine 3’, 5’-monophosphate (cGMP), in osteoblasts. However, the role of cGMP in the regulation of estrogen biosynthesis, whose deficiency is a major cause of osteoporosis, remains unclear. Here, we found that the prenylated flavonoids, 3-O-methoxymethyl-7-O-benzylicaritin (13), 7-O-benzylicaritin (14), and 4‘-O-methyl-8-isopentylkaempferol (15), which were synthesized using icariin analogs, promoted estrogen biosynthesis in osteoblastic UMR106 cells, with calculated EC50 values of 1.53, 3.45, and 10.57 mM, respectively. 14 and 15 increased the expression level of the bone specific promoter I.4-driven aromatase, the only enzyme that catalyzes estrogen formation by using androgens as substrates, in osteoblastic cells. 14 inhibited phosphodiesterase 5 (PDE5), stimulated intracellular cGMP level and promoted osteoblast cell differentiation. Inhibition of cGMP dependent-protein kinase G (PKG) abolished the stimulatory effect of 14 on estrogen biosynthesis and osteoblast cell differentiation. Further, PKG activation by 14 stimulated the activity of SHP2 (Src homology 2 domain-containing tyrosine phosphatase 2), thereby activating Src and ERK (extracellular signal-regulated kinase) signaling and increasing ERK-dependent aromatase expression in osteoblasts. Our findings reveal a previously unknown role of cGMP in the regulation of estrogen biosynthesis in the bone. These results support the further development of 14 as a PKG-activating drug to mimic the anabolic effects of mechanical stimulation of bone in the treatment of osteoporosis.